2021
DOI: 10.3390/ijms22189781
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Extract Suppresses IL-1β-Induced Inflammatory Signaling Pathways in Human Chondrocytes and Ameliorates the Cartilage Destruction of Experimental Osteoarthritis in Rats

Abstract: We investigated the effects of adipose-derived extract (AE) on cultured chondrocytes and in vivo cartilage destruction. AE was prepared from human adipose tissues using a nonenzymatic approach. Cultured human chondrocytes were stimulated with interleukin-1 beta (IL-1β) with or without different concentrations of AE. The effects of co-treatment with AE on intracellular signaling pathways and their downstream gene and protein expressions were examined using real-time PCR, Western blotting, and immunofluorescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…In addition, the effect of hsMSCs on cartilage anabolism/ catabolism was not shown, while PMSCs improved anabolism and inhibited catabolism to protect cartilage from degradation. Similar in vitro studies have shown that chondrocytes were modeled by IL-1β and treated with MSC-CM (Ohashi et al, 2021;Sampath et al, 2021;Lofgren et al, 2022). The decreased expression of MMP13 and Adamts5 and increased expression of Col2 were observed (Sampath et al, 2021), which showed similar tendency of results with ours.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, the effect of hsMSCs on cartilage anabolism/ catabolism was not shown, while PMSCs improved anabolism and inhibited catabolism to protect cartilage from degradation. Similar in vitro studies have shown that chondrocytes were modeled by IL-1β and treated with MSC-CM (Ohashi et al, 2021;Sampath et al, 2021;Lofgren et al, 2022). The decreased expression of MMP13 and Adamts5 and increased expression of Col2 were observed (Sampath et al, 2021), which showed similar tendency of results with ours.…”
Section: Discussionsupporting
confidence: 87%
“…Inflammation is a key driver in the pathogenesis of kOA, characterized by increased levels of proinflammatory cytokines (e.g., IL-1β), which, in turn, induces ECM degradation through enhanced production of catabolic enzymes ( Wehling et al, 2009 ; Goldring and Otero, 2011 ; Kapoor et al, 2011 ; Rigoglou and Papavassiliou, 2013 ). Therefore, many studies have applied IL-1β to establish in vitro model of kOA on chondrocytes, since IL-1β induces inflammatory damage on chondrocytes and impels chondrocytes to catabolic MMP1 and MMP13 to destruct cartilage matrix ( Guan et al, 2018 ; Zhang et al, 2020 ; Chen et al, 2021 ; Ohashi et al, 2021 ; Pferdehirt et al, 2022 ). In this study, IL-1β was used to treat chondrocytes, resulting in increased chondrocyte degradation (Adamts4, Adamts5, MMP13) and decreased synthesis (Col2, Sox9), indicates the kOA-like phenotype of chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1 α is a bifunctional cytokine present in resting cells under physiological conditions. IL-1β can upregulate the expression of most cytokines, including COX-2, NO, TNF-α, prostaglandin E2 (PGE2), and IL-6 through the mitogen-activated protein kinase (MAPK) pathway [ 182 ]. It also increases the synthesis of ADAMTS proteases and MMPs and inhibits the synthesis of proteoglycan [ 183 ] ( Figure 2 ).…”
Section: Adamts and Inflammation In Oamentioning
confidence: 99%
“…The low reported survival rate of MSCs implanted into knee joints[ 17 ] and their tendency to migrate to the synovium and menisci, not solely to the damaged cartilage itself[ 53 ], further strengthens the doubt over their role in direct differentiation into neocartilage. Instead, regeneration is likely promoted by ASCs via immunomodulatory mechanisms and secretion of chondroprotective biomolecules[ 52 , 54 , 55 ].…”
Section: Ascs: Mechanism Of Actionmentioning
confidence: 99%